Blood Pressure Pattern and Prevalence of Hypertension amongst Apparently Healthy Primary School Pupils in Abuja, Nigeria - Nubwa Yusufu Papka; Iretiola Bosede Babaniyi; Henry A. Aikhionbare; John Toluwani Oladele; Josephat Maduabuchi Chinawa (Nigerian Postgraduate Medical Journal)
Objectives: The objective of this study was to determine the blood pressure (BP) pattern and prevalence of hypertension amongst apparently healthy primary school pupils in Abuja. Methodology: This was a descriptive, cross-sectional study carried out on apparently healthy primary school children aged 6–12 years. BP was measured using a standard mercury sphygmomanometer according to standard guidelines. Data were analysed using SPSS version 17.0. Pearson’s correlation coefficient (r) and analysis of variance were used to determine the relationship between BP and various variables where applicable. P = 0.05 was considered statistically significant. Results: Out of 1011 pupils recruited for the study, 457 (42.2%) were male. The mean systolic and diastolic BP (SBP and DBP) increased significantly with age from 94.5 mmHg to 101.0 mmHg and from 61.5 mmHg to 65.3 mmHg from 6 to 12 years for SBP and DBP, respectively (P < 0.05). The prevalence of high BP was 9.1%. Age was the only predictor of SBP (β = –0.629, 95% confidence interval [CI] –1.115, –0.142), while age, height and body mass index (BMI) were the predictors of DBP (β = –0.686, 95% CI of –1.152, –0.221; β = 0.490, 95% CI of 0.172, 0.809; β = 1.753, 95% CI of 0.374, 3.160) for age, height and BMI, respectively, at P < 0.05. Conclusion: The predictors of SBP and DBP as shown in this study support the recommendations by various reports for taking body size into consideration in developing reference values for various populations. Age and body size are important determinants of BP in children. Its measurement should be encouraged in schools.